Food systems emissions in Colombia and their reduction potential: A country profile - Martius, C.; Wassmann, R.; Mwambo, F.M.; Pingault, N.; Guérin, L. (CIFOR-ICRAF, 2023)
Colombia ́s food system emissions remained stable in absolute level over the past decade (2010-2020) at around 183 MtCO2 eq. Although the relative importance of these food system emissions decreased since 2010 in line with the broader economic development, in 2020 they still represented two thirds (62%) of total national emissions. The largest sources of emission in Colombia’s food system are net forest conversion (45% of total emissions), enteric fermentation (26%), manure management in the broad sense (9%), and food waste disposal (6%). Altogether, these four categories account for 86% of all food system emissions.